A 20-year latency between hysterectomy for endometrial adenocarcinoma and solitary pulmonary metastasis: a case report. Issue 2 (5th February 2021) - Kodia, Karishma; Richards, Stephanie; Pinto, Andre; Pearson, Joseph M; Nguyen, Dao M
Abstract: We present a rare case pulmonary metastasis of an early stage endometrial cancer nearly 20 years after curative surgical resection. Our patient had a remote history of hysterectomy for endometrial cancer in 1998 and later had Stage 1B right upper lobe lung cancer treated with lobectomy and adjuvant chemotherapy in 2014. She was found to have an enlarging nodule in the left upper lobe in 2018, which was thought to be another primary lung cancer. She underwent left upper lobe segmentectomy for an intraoperative diagnosis of adenocarcinoma by diagnostic wedge resection of the lung nodule. Final pathologic examination of the resected tumor demonstrated an endometrial adenocarcinoma. It is important for thoracic surgeons to remain vigilant, keeping secondary lung cancer in the differential diagnosis for patients with complex oncologic histories.